A new aporphine alkaloid from the leaves of Alseodaphne corneri Kosterm (Lauraceae). Issue 14 (6th April 2016) - Nafiah, Mohd Azlan; Tan, Siow-Ping; Khoo, Jennie Hui-Chen; Hasnan, Muhammad Hafiz Husna; Awang, Khalijah; Hadi, A. Hamid A.; Ahmad, Kartini
Graphical abstract: Highlights: A new aporphine alkaloid, demethoxyglauvine, was reported from A . corneri . Seven known isoquinoline alkaloids were also reported in this manuscript. Compounds1 and7 were first time isolated from leaves of A. corneri . A possible biogenetic pathway of compound1 was described. Abstract: A new aporphine alkaloid, demethoxyglauvine (1 ), along with seven known isoquinoline alkaloids, was isolated from the alkaloid crude extract of the leaves of Alseodaphne corneri . Their structures were determined by extensive spectroscopic analysis including 1D and 2D NMR ( 1 H– 1 H COSY, HSQC, and HMBC), mass spectrometry, and by comparing with the published data. A possible biogenetic pathway for the formation of1 was proposed.